Desain Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) pada Pelajaran Al-Qur'an Hadits Tingkat Madrasah Ibtida’iyah (MI) - Uci Nurfadhilah; Sri Agung Mulyati; Herlina Putri (PT. Pusmedia Group Indonesia, 2023)
Madrasah Ibtidaiyah is a formal institution based on the learning process on Islamic values and has a clear vision and mission. Al-Qur'an Hadith lessons in Madrasah Ibtidaiyah is one of the subjects that emphasizes the ability to read and write the Al-Qur'an and Hadith correctly as well as memorization of short letters in the Al-Qur'an, simple introduction to the meaning or meaning of these short letters and hadiths about praiseworthy morals to be practiced in everyday life through exemplary and habituation. This research uses a qualitative approach. The data collection technique in this research is library research. Based on some of the results of previous research, there are several obstacles found, namely: educators who tend to be more active and passive students, educators use methods that are less varied, so that students are less active in learning classes. Therefore, to improve student learning outcomes, the right learning model is needed. One of the learning models that is suitable for Al-Qur'an Hadith subjects is the Numbered Head Together (NHT) type cooperative learning model. Keywords: Learning Design; Cooperative Numbered Head Together; Al-Qur'an Hadith lesson.